Association between ACE and ACTN3 genes polymorphisms and athletic performance in elite and sub-elite Chinese youth male football players - Yang,Shidong; Lin,Wentao; Jia,Mengmeng; Chen,Haichun (PeerJ, 2023)
Background Previous studies have shown controversial relationships between ACE I/D and ACTN3 R577x polymorphisms and athletic performance. Therefore, the aim of this study was to assess athletic performance indicators of Chinese youth male football players with different ACE and ACTN3 gene profiles. Methods and Materials This study recruited 73 elite (26 13-year-olds, 28 14-year-olds, and 19 15-year-olds) and 69 sub-elite (37 13-year-olds, 19 14-year-olds, and 13 15-year-olds) and 107 controls (63 13-year-olds, and 44 14-year olds aged 13–15 years, all participants were of Chinese Han origin. We measured height, body mass, thigh circumference, speed, explosive power, repeat sprints ability, and aerobic endurance in elite and sub-elite players. We used single nucleotide polymorphism technology to detect controls elite and sub-elite players’ ACE and ACTN3 genotypes, Chi-squared (χ2) tests were employed to test for Hardy-Weinberg equilibrium. χ2 tests were also used to observe the association between the genotype distribution and allele frequencies between controls and elite and sub-elite players. The differences in parameters between the groups were analyzed using one-way analysis of variance and a Bonferroni’s post-hoc test, with statistical significance set at p ≤ 0.05. Results (1) The genotype distribution of the ACE I/D and ACTN3 R577x polymorphisms in controls, elite and sub-elite football players were consistent with Hardy-Weinberg equilibrium, except for the ACE genotype distribution of sub-elite players. (2) The RR and DD genotypes were significantly different between elite and sub-elite players (p = 0.024 and p = 0.02, respectively). (3) Elite players were more likely to have the RR genotype and less likely to have the DD genotype compared with sub-elite players. (4) Both elite and sub-elite RR players’ Yo-yo intermittent recovery level 1 (YYIR1) running distance was significantly longer than that of RX players (p = 0.05 and p = 0.025, respectively). However, there was no significantly different in YYIR1 running distance between elite and sub-elite RR players. (5) Elite XX players’ VO2 max was significantly higher than that of RX and sub-elite players. Conclusion These results indicate that ACE I/D and ACTN3 R577x polymorphisms are not associated with muscle power in Chinese elite and sub-elite players. The XX genotype of ACTN3 is associated with the aerobic endurance of elite players.
Keywords: α-actinin-3; Angiotensin converting enzyme; Genotype; Muscle phenotype